Путешествия в некоторые отдаленные страны света Лемюэля Гулливера, сначала хиркрга, а потом капитана нескольких кораблей; Travels Into Several Remote Nations of the World by Lemuel Gulliver, First a Surgeon, and then a Captain of Several Ships: роман - Swift J. Jonatan (English Fiction Collection)
Книга на английском языке.